Religious Activities and the Construction of Religious Character Among Children with Special Needs in Inclusive Schools in Palembang - Lianawaty; Munir; Ema Yudiani; Maryamah; Muhammad Torik (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Inclusive education seeks not only to ensure equal access to education but also to foster the holistic development of children with special needs, including their religious character. However, limited adaptive educational strategies and the absence of systematic frameworks for integrating religious activities into inclusive learning environments continue to challenge the effectiveness of religious character education. This study aims to examine the construction of religious activities, explore their implementation, and analyze their contributions to the development of religious character among children with special needs in inclusive schools in Palembang, Indonesia. Employing a qualitative multiple-case study design, the research was conducted at SD Negeri 30 Palembang and SMP Negeri 13 Palembang. Data were collected through in-depth interviews, participant observations, questionnaires, and document analysis involving school principals, teachers, special education teachers, parents, and children with special needs. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while trustworthiness was ensured through triangulation and member checking. The findings reveal that religious activities are systematically constructed through students' needs assessment, adaptive learning objectives, contextual religious content, differentiated instructional strategies, and collaborative partnerships among schools and families. Their implementation is strengthened through habituation, teacher role modelling, individualized mentoring, and inclusive school culture. These practices contribute significantly to the development of worship habits, spiritual awareness, discipline, responsibility, empathy, respect, and positive social interaction among children with special needs. The study concludes that religious activities constitute an adaptive and sustainable educational framework for fostering religious character within inclusive schools. The findings contribute to the advancement of inclusive religious education by providing a contextual model for integrating religious values into character development among children with special needs.